Ditundukkan, Terasing, dan Imbalan Tak Setara: Praktik Pekerja Digital Media Sosial Suara.com - Aprilie, Theresia; Eddyono, Aryo Subarkah (Program Studi Ilmu Komunikasi, 2024)
The use of social media in mainstream media has become commonplace in the digital age. This raises issues of copyright, quality, and exploitation of digital labour, such as low wages and high workloads. This research aims to reveal the practices of the digital labour in managing Suara.com's social media accounts based on Fuchs' digital labour theory. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with digital labour managing Suara.com's social media accounts, non-participant observation, and analysis of internal documents and related publications. Through the study of the results associated with Christian Fuchs' digital labour theory, the results show that the digital labours are exploited in terms of workload, the absence of boundaries between personal life and work, and equal recognition of work results. This practice reflects the aspects of the digital labour exploitation, namely coercion, alienation, and appropriation.